Giant mesenteric cystic lymphangioma: a rare cause of intra-abdominal catastrophe - Gunasekaran, Gopalakrishnan; Naik, Debasis; Kandhasamy, Sakthivel Chinnakkulam; Soren, Dhirendra Nath (International Surgery Journal, 2019)
Lymphangiomas are uncommon benign tumours and occur mainly in children with the most common sites being head and neck followed by the axilla and mediastinum. Intra-abdominal lymphangiomas are rare. Clinical presentation is diverse ranging from incidentally discovered abdominal mass to symptoms of acute abdomen. Life threatening complications are more likely to develop in children. We here present a rare case of giant mesenteric cystic lymphangioma causing intra-abdominal catastrophe in an adult.